2015
DOI: 10.1186/s12986-015-0021-6
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of sugar sweetened beverage is associated with incidence of metabolic syndrome in Tehranian children and adolescents

Abstract: BackgroundIntakes of high sugar-sweetened beverages (SSBs) in adults can escalate risk of metabolic syndrome (MetS); however, data of longitudinal studies in children and adolescents are lacking. In this study we assessed consumption of SSBs in relation to incidence of MetS among children and adolescents during a 3.6 year follow-up.MethodsThis study was a population-based longitudinal study, in which 424 subjects, aged 6–18 years, from the Tehran Lipid and Glucose Study with complete data on dietary intake, bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
113
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(126 citation statements)
references
References 46 publications
7
113
0
6
Order By: Relevance
“…In 2 studies under-reporters were included in the analysis but with adjustment for underreporting, and in 4 studies under-reporters were excluded. Five studies used BMI as body weight outcome [20,21,22,23,24], 5 BMI Z-score [25,26,27,28,29], 3 body fat [30,31,32], 3 waist circumference [33,34,35], and 1 weight-for-height z-score [36] (table 1). Almost all (94%) of the articles showed a positive association between SSB intake and body weight measures, meaning that a higher SSB consumption lead to a higher degree of adiposity.…”
Section: Resultsmentioning
confidence: 99%
“…In 2 studies under-reporters were included in the analysis but with adjustment for underreporting, and in 4 studies under-reporters were excluded. Five studies used BMI as body weight outcome [20,21,22,23,24], 5 BMI Z-score [25,26,27,28,29], 3 body fat [30,31,32], 3 waist circumference [33,34,35], and 1 weight-for-height z-score [36] (table 1). Almost all (94%) of the articles showed a positive association between SSB intake and body weight measures, meaning that a higher SSB consumption lead to a higher degree of adiposity.…”
Section: Resultsmentioning
confidence: 99%
“…These solid foods have high content of energy, added sugar, saturated fat, and salt. The association between sugar sweetened beverages and MetS among children and adolescents was investigated in another study, published recently (41). Sugar sweetened beverages were not included in snack consumption; nor were foods with high nutritional value, such as fruits, vegetables, and dairy products, considered as snacks.…”
Section: Dietary Assessmentmentioning
confidence: 99%
“…[4][5][6] Soft drink consumption may be a proxy marker of an unhealthy lifestyle or may lead to metabolic syndrome through molecular and physiological pathways which predispose to obesity, dyslipidaemia, and dysglycaemia. 12 Similarly, a prospective cohort study of 9514 adults in the USA found individuals in the highest tertile of ASB intake to have a greater risk of metabolic syndrome (RR 1.34, 95% CI 1.24-1.44) after a 9-year follow-up. For example, a prospective cohort study of middle-aged adults in the USA found a non-significant association between SSB intake and development of metabolic syndrome (OR 1.62, 95% CI 0.96-2.74) in a subgroup of 3184 participants.…”
Section: Introductionmentioning
confidence: 97%